Development of Literacy Booth Media to Enhance Understanding of Fiqh Learning Materials in Madrasah Tsanawiyah - Helmy, Helmy; Zainuddin, Fauziah; Nuraeni, Nuraeni (Educational Journal of Learning Technology, 2025)
This study aims to evaluate the validity and practicality of literacy booth media in improving students’ understanding of fiqh, specifically on Hajj rituals. Data were collected through questionnaires and interviews using the ADDIE-based Research and Development (R&D) model. The media was validated by three experts: content (97.5%), media design (85%), and language (97.5%). Results show that the literacy booth effectively enhances student engagement and comprehension, making it a practical tool for teaching fiqh to seventh-grade students.